Vancomycin Cerebrospinal Fluid Pharmacokinetics in Children with Cerebral Ventricular Shunt Infections - Autmizguine, Julie (2014)
This study described the cerebrospinal fluid (CSF) exposure of vancomycin in 8 children prescribed intravenous vancomycin therapy for cerebral ventricular shunt infection. Vancomycin CSF concentrations ranged from 0.06 to 9.13 mg/L and the CSF: plasma ratio ranged from 0 to 0.66. Two children out of three with a staphylococcal CSF infection had CSF concentrations > minimal inhibitory concentration at the end of the dosing interval.